Arterial repair after bare-metal stent implantation in peripheral arteries is delayed compared to that in coronary arteries: A case report of pathological evaluation. Issue 3 (September 2016) - Ishihara, Takayuki; Iida, Osamu; Shiraki, Tatsuya; Fujita, Masashi; Inoue, Katsumi; Uematsu, Masaaki
Abstract: Despite widespread use of endovascular therapy with bare-metal stent (BMS) implantation in patients with peripheral artery disease (PAD), arterial healing has not been well examined in this setting. An 84-year-old man with PAD received BMS implantation at the right external iliac artery (EIA, Epic 8.0 mm × 100 mm) and superficial femoral artery (SFA, SMART Control 8.0 mm × 150 mm). However, he died of lobar pneumonia 81 days later. Pathological evaluation was conducted at BMS implantation sites. At the distal part of Epic site in the EIA, neointimal formation was seldom observed. A small amount of fibrin deposition was seen around stent struts without apparent smooth muscle cell proliferation or surface endothelial cell coverage. In contrast, at the middle part of distal SMART site in the SFA, most of the stent struts were completely covered with moderate amount of neointima which was composed of a lot of smooth muscle cells and extracellular matrix on the plaque-free wall. However, on the contralateral calcified plaque site, a lot of fibrin components were still observed over the surface of thin neointima and only rough smooth muscle cells were scatteringly infiltrated. Furthermore, incomplete endothelial cell coverage was seen on the surface. Arterial repair after BMS implantation in peripheral arteries was extremely delayed. <Learning objective: An 84-year-old man with peripheral artery disease received bare-metal stent (BMS) implantation in peripheral arteries. Pathological evaluation 81 days later showed heterogeneous neointimal coverage formation with incomplete coverage, especially at the vessel portions with significant plaque burden. In these portions, endothelial cell coverage was also incomplete. Moreover, some malapposed struts were observed. Arterial repair after BMS implantation in peripheral arteries was extremely delayed.>